Spinal cord protection by normothermic artery bypass and visceral-anastomosis-first strategy in thoracoabdominal aortic aneurysm repair - Shuai Zhang; Yuan Li; Yongkang Zhou; Cuntao Yu; Xiaogang Sun; Hongwei Guo; Yi Chang; Dong Zhao; Jing Sun; Xiangyang Qian (BMC Cardiovascular Disorders)
Abstract Background Spinal Cord Injury is a disastrous complication of thoracoabdominal aortic aneurysm surgery. This study is to assess the effectiveness and safety normothermic artery bypass and visceral-anastomosis-first strategy for thoracoabdominal aortic aneurysm repair. Methods Normothermic artery bypass and visceral-anastomosis-first strategy prioritizes the reconstruction of visceral and other distal vessels, with intercostal arteries serving as the physiological blood supply at high pressure during this period. Reconstruction of intercostal arteries and proximal anastomosis is then performed, ensuring the longest possible physiological blood supply to the spinal cord. From July 2019 to December 2023, we retrospectively analyzed early postoperative complications in two groups of patients undergoing thoracoabdominal aortic aneurysm repair using the new strategy compared to normothermic iliac artery perfusion, clarifying the protective effects of the new strategy on visceral organs, especially the spinal cord. Results The incidence of paraplegia was significantly lower in the NABP group than in the normothermic iliac perfusion (NIP) group (0.00% vs. 9.72%, p = 0.047), and the duration of postoperative mechanical ventilation was significantly lower in the NABP group than in the NIP group (p = 0.004). In addition, we found that the incidence of gastrointestinal adverse events was significantly lower in the NABP group than in the NIP group (7.32% vs. 45.83%, p < 0.001). Typically, patients’ lactate levels returned to normal within approximately 48 h postoperatively. Although not statistically significant, lactate fell to normal more quickly in the NABP group after surgery. Conclusions The treatment of thoracoabdominal aortic aneurysm through open surgery is still an important method and remains difficult. The data we have suggests that our approach of normothermic artery bypass and visceral-anastomosis-first strategy can lower the risk of spinal cord injury complications.